(untitled) (Global Journal of Management and Business Research, 2019)
The main aim of this paper is to enhance the concept of organizational development (OD) in the mind of the readers, as a field of planned change that aims to enhance organizational effectiveness for the organizations. Also, to review the roots of OD and CM, which one of them is the base for the other, based on numerous similarities and differences, that is clarify the relationship between OD and CM. The conceptual literature shades the light on the historical back ground of OD and CM, that focusing on the emergence of CM as a service provided by some advisory organizations in private sector, where OD has evolved mainly in the public sector. The shift or movement from OD to the new trend CM started in the mid of 1980s.Finally a brief discussion and conclusions were included.